Introducing soil air injection device to reduce carbon footprint of rice production system in China. (20th June 2023) - Tang, Jichao; Li, Chengfang; Tan, Wenfeng; Cao, Cougui; Zhang, Weijian; Zhang, Lu; Hu, Quanyi; Xiong, Hang; Luo, Jing; Song, Wenjie; Liu, Tianqi
Abstract: Improving soil aeration in paddy fields using mechanical device reduces methane (CH4 ) emissions, whereas it also increases the contribution of other sources (device production, agricultural inputs, etc.). Here, this study applied the life cycle assessment (LCA) method to evaluate the carbon footprint of a soil air injection device (SAID) in rice field. We further analyzed the prospects of this device in promoting carbon emission reduction in China's main rice-producing areas, which was combined with economic benefit calculation and revised knowledge-attitude-practice (KAP) model. Results showed that the reduction of net carbon emissions from paddy fields under SAID treatment was 4.51–241.95% higher than the total carbon emissions from the production, transportation, operation, and recycling of SAID. The economic output of using SAID in rice fields could just offset the cost of it. With reasonable government subsidies (142.80–349.95 yuan SAID −1 yr −1 ), SAID can reduce carbon emissions from Chinese rice fields by ∼ 41.60 Tg CO2 -eq yr −1 . This study suggests that using SAID in some rice planting areas in China may be an effective way to reduce carbon emissions. Graphical abstract: Image 1 Highlights: SAID could reduce carbon footprint of rice production system. The limiting factor for the development of SAID is mainly low economic efficiency. The cost of emission reduction in each region is 0.16–6.07 yuan per kg CO2 -eq.